Recombinant Factor VIIa Reduces Bleeding after Blunt Liver Injury in a Pig Model of Dilutional Coagulopathy under Severe Hypothermia. - Henri M H Spronk; Till Braunschweig; Rolf Rossaint; Dirk C Wüst; Rene van Oerle; Brian Lauritzen; Rene Tolba; Oliver Grottke (PLoS ONE, 2015)
Recombinant factor VIIa (rFVIIa) is registered for use in haemophilia with inhibitors and other rare bleeding disorders, but has also been used in various other clinical conditions to terminate life-threatening bleeding. Underlying conditions (e.g. coagulopathy) and dosing may affect treatment efficacy. The objective of the present study was to evaluate the impact of increasing doses of rFVIIa on blood loss and coagulation assays in haemodiluted and hypothermic pigs undergoing blunt liver injury.A grade III blunt liver injury was induced in 28 pigs after 70% haemodilution and cooling to 32.6-33.4°C. Ten minutes after trauma, animals randomly received placebo or 90, 180 or 360 μg/kg rFVIIa. Global coagulation parameters, thromboelastometry (TEM) and plasma thrombin generation (TG) were determined at different time points during the observation period of 120 minutes.Total blood loss was significantly lower following 90 μg/kg rFVIIa (1206 [1138-1470] mL) relative to placebo (2677 [2337-3068] mL; p<0.05), with no increased effect with higher dose levels of rFVIIa. Following trauma and haemodilution, coagulation was impaired relative to baseline in both TEM and TG analysis. At 60 and 120 minutes after trauma, TEM variables improved in the rFVIIa-treated animals compared with the placebo group. Similarly, rFVIIa improved coagulation kinetics in TG. As was observed with blood loss, no significant effect between different rFVIIa dose levels was found in TEM or TG. Macro- and microscopic post-mortem examination did not reveal any signs of thromboembolic events.Early administration of 90 μg/kg rFVIIa reduced blood loss in pigs undergoing blunt liver injury even after severe haemodilution and hypothermia, with no further effect of higher dose levels. Coagulation assays showed impaired coagulation in coagulopathic animals, with a dose-independent improvement in animals treated with rFVIIa.